2007
DOI: 10.1002/prot.21488
|View full text |Cite
|
Sign up to set email alerts
|

Structural assessment of glycyl mutations in invariantly conserved motifs

Abstract: Motifs that are evolutionarily conserved in proteins are crucial to their structure and function. In one of our earlier studies, we demonstrated that the conserved motifs occurring invariantly across several organisms could act as structural determinants of the proteins. We observed the abundance of glycyl residues in these invariantly conserved motifs. The role of glycyl residues in highly conserved motifs has not been studied extensively. Thus, it would be interesting to examine the structural perturbations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 53 publications
(87 reference statements)
1
2
0
Order By: Relevance
“…The analysis showed significantly lower evolutionary divergence rates of L-disallowed Gly as compared to L- allowed ones at both pathogenic and benign sites, though relatively greater at pathogenic sites (Figure 2A, Table S1). This was consistent with the earlier reports wherein the Gly present in the conserved regions of proteins tended to exhibit L-disallowed conformation 24 .…”
Section: L-disallowed Glycyls Are Evolutionarily More Conserved Than ...supporting
confidence: 93%
See 2 more Smart Citations
“…The analysis showed significantly lower evolutionary divergence rates of L-disallowed Gly as compared to L- allowed ones at both pathogenic and benign sites, though relatively greater at pathogenic sites (Figure 2A, Table S1). This was consistent with the earlier reports wherein the Gly present in the conserved regions of proteins tended to exhibit L-disallowed conformation 24 .…”
Section: L-disallowed Glycyls Are Evolutionarily More Conserved Than ...supporting
confidence: 93%
“…Mutation of Gly to L-Ala, but not to D-Ala, leads to loss of structural and functional attributes of protein 23 . Prakash et al 24 has shown that the glycyl residues occurring in the evolutionarily invariant peptides in bacteria tend to be buried and were moderately more frequent in the L-disallowed regions. More recently, Lakshmi et al has claimed that the small size of the Gly, regardless of L-allowed or L-disallowed conformation, could likely have guided their evolutionary selection in conserved protein families 25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation